PROTOTYPE OF WATER PIPE LEAKAGE DETECTOR USING FLOWMETER SENSOR BASED ON ARDUINO UNO - Widayaka, Parama Diptya; Jauhari, Lutfi (BEST, 2020)
Water pipe leakage causes financial loss for the user such as PAM or PDAM. YF-S201B flowmeter sensor is a water flow sensor made of plastic with a rotor and hall effect sensor inside. The rotor will spin when the water flow through the sensor. The speed of rotor spin is proportional to the water flow. The hall effect based sensor can be used to detect water flow up to 30 liter/minute (1.800L/hour) thus, the sensor can be used to control the water flow in distribution system and water debit monitoring. The principle of prototype is the placement of sensor before the leakage and after leakage position to obtain different value of water debit. The system will send a short message automatically to the phone if water leakage is detected in the pipeline.